Quasinormal Modes of the Planar Black Holes of a Particular Lovelock Theory - Wen, Dan [UNESP]; Lin, Kai; Qian, Wei-Liang [UNESP] (Iop Publishing Ltd, 2018)
In this work, we study the scalar quasinormal modes of a planar black hole metric in asymptotic anti-de Sitter spacetime derived from a particular Lovelock theory. The quasinormal frequencies are evaluated by adopting the Horowitz-Hubeny method as well as a matrix formalism. Also, the temporal evolution of small perturbations is studied by using finite difference method. The roles of the dimension of the spacetime, the parameter of the metric k, as well as the temperature of the background black hole, are discussed. It is observed that the particular form of the metric leads to quasinormal frequencies whose real parts are numerically insignificant. The black hole metric is found to be stable against small scalar perturbations.
Keywords: quasinormal modes; Lovelock theory; Horowitz-Hubeny method; matrix method